EFEKTIVITAS KEBIJAKAN PROGRAM MAKANAN BERGIZI GRATIS (MBG): EVALUASI BERDASARKAN PRINSIP TATA KELOLA YANG BAIK - Mohammad Aviv Mustaghfirin (Supremasi Hukum: Jurnal Penelitian Hukum, 2026)
The Free Nutritious Food (MBG) Program is the flagship program of the Prabowo Subianto-Gibran Rakabuming Raka government which will be launched in 2025 with a budget allocation of Rp 71 trillion. This program aims to address chronic nutrition problems, especially stunting, and improve the quality of Indonesia's human resources. This study analyzes the implementation of the MBG Program from the perspective of governance. The research method uses normative juridical research with public policy analysis and study of regulatory literature, policy documents, and related academic studies. The results of the study show that MBG has several challenges from the principles of good government, namely transparency, accountability, and community participation. In transparency, challenges stem from the complexity of the reporting system, the difference in the price of foodstuffs in each region and the indication of price mark-ups during procurement and price distribution. In accountability, challenges stem from  the lack of internal auditor capacity at the regional level and the lack of a deterrent effect for MBG accountability violators. In community participation, challenges stem from the lack of community participation and public consultation on MBG Program planning. The collaboration strategy between state institutions is the existence of a centralized system for information exchange, cross-sectoral task forces at the national and regional levels, and the development of a platform information system.